Assessing the ability of acidulated fluoride solutions to etch glass-based restorative materials - a pilot study - Mokhtar, Kasmawati (2006)
Topical fluorides have been used widely in dentistry for over fifty years, and are credited with having contributed greatly to the marked decline in caries prevalence recorded in most industrialized countries over the last three decades (Fejerskov, 1981 ). A wide variety of forms of topical fluoride have been developed in an effort to provide differing modes of action in caries control. For example, the low concentrations of fluoride in dentifrices and mouth rinses have been designed to provide prophylactic protection against caries across the population, though are effective only to a limited degree. More advanced rates of caries development have lead to the formulation of high fluoride concentration gels and varnishes subject to professional application on prescription. One such gel containing sodium fluoride in an acidulated base (called acidulated phosphate fluoride or APF), was widely used until it was found to etch glass-based restorative materials. Yet, such a formulation has been shown to provide a much higher level of fluoride uptake into tooth structure, (Pai, 1995) and to protect against strong acidic challenges such as dental erosion than its neutral counterpart. The studies to evaluate the latter effect were by Jones et al (2002) and Mok et al (2001) who reported the reduction in the loss of enamel surface to a significant extent with the application of acidulated topical fluoride gel prior to simulated endogenous and exogenous acid exposure.